Modelling the survivorship of Nigeria children in their first 10 years of life (2016)
Introduction: Several studies have attributed social demographic and environmental characteristics to differentials in children mortality rates worldwide but there is paucity of information on modelling of children survival in Nigeria. In this study we modelled children survival in Nigeria for first five years of life and predicted their chances of survival in their sixth to tenth years of life. Methods: We used the data from the 2013 Nigeria Demographic and Health Survey to carry out a retrospective analysis of children survival. We computed the probability of survival and mortality rates for the first five years and predicted survivals for 6th to 10th years of life using life table techniques and compared our estimates with those obtained using Brass indirect techniques. Results: The probability of a child surviving up to exact age 1 and 5 were 0.9212 (95% CI: 0.919-0.923) and 0.8583 (95% CI: 0.855-0.861), respectively. About 142 of every 1000 children would not make their tenth birthday in Nigeria. We found higher survivorship trend among female children than the males with higher rates in Southern Nigeria than in the Northern parts. The estimates of probabilities of survival from age 1 to 5 from the fitted curves agreed very closely with those obtained from Brass indirect techniques as the variability was less than 2%. Conclusion: Child mortality is high in Nigeria with fewer children deaths among females. Probability of not attaining age 10 in South West is lower than chances of not marking first birthday in North West zone. Efforts must be concentrated in reversing the worrisome survival trend in Nigeria especially in the Northern parts of the country.